Multiple data-collection methods as a source of insight into grammar teaching - Ismail, Fauziah (Penerbit UTM, 2008)
The issue of grammar teaching in Language Teacher Education (LTE) needs to take into account the factors that can influence teacher trainees’ pedagogical choices and decision-making when teaching grammar in the classrooms. Language researchers (Ellis, 1998; Borg, 1998, 1999 & 2006; Burgess, 2002) have investigated how language teachers’ cognition, education experience and second language (L2) competence can influence their teaching of grammar. These researchers explored how language teachers approach the teaching of grammar in their classes and the reasons affecting their decisions. However, few research have been carried out on the factors that influence how teacher trainees approach the teaching of grammar during their practicum. Exploring teacher trainees’ pedagogical systems, grammar teaching and the reasons that underpin their pedagogical choices and decision-making can provide insights into the factors that underlie teacher trainees’ behavior. This kind of research can provide answers to what extent pre-LTE, formal training in LTE and teacher trainees’ cognition,beliefs and values shape their grammar teaching and classroom practices. This paper presents the qualitative approach of data collection on the way teacher trainees conduct grammar teaching in their classrooms and the reasons that underpin their pedagogical choices and decisions in teaching grammar. It discusses how the research is grounded in the realities of classroom practice and highlights the strengths of adopting a qualitative approach in exploring how teacher trainees approach the teaching of grammar in their classrooms. This paper also presents the perspectives of the teacher trainees on the factors affecting their instructional decisions.